2012
DOI: 10.1177/197140091202500305
|View full text |Cite
|
Sign up to set email alerts
|

Neuroimaging Assessment of Spasticity Developed after Acquired Brain Injuries and Multiple Sclerosis

Abstract: This study evaluated whether different imaging techniques correlate with specific variables routinely used to grade the types and complexities of patient conditions in neurorehabilitation services and their clinical outcomes, and if there are radiological patterns, topography or distribution of the lesions correlated to spasticity. The cohort studied included 75 patients, 38 patients with multiple sclerosis (MS) and 37 patients with acquired brain injuries (ABI) referred to the neurorehabilitation department f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 17 publications
0
3
0
Order By: Relevance
“…The degree of spasticity improved in all subjects after the injection of botulin toxin. Their mean spasticity score in the Disability Assessment Scale improved from 2.5 (2)(3) previously to the injection to 1 (0-2) post-injection.…”
Section: Resultsmentioning
confidence: 91%
See 1 more Smart Citation
“…The degree of spasticity improved in all subjects after the injection of botulin toxin. Their mean spasticity score in the Disability Assessment Scale improved from 2.5 (2)(3) previously to the injection to 1 (0-2) post-injection.…”
Section: Resultsmentioning
confidence: 91%
“…It is estimated that around 75% of patients with severe traumatic brain injury, 20% of stroke survivors and 60% of subjects with moderate to severe Multiple Sclerosis require specific spasticity treatment [2].…”
Section: Introductionmentioning
confidence: 99%
“…Multiple MS studies conducted neuroimaging to address the brain network connectivity of cognitive functions, pain, and fatigue, but few evaluated spasticity. A retrospective study reported three main regions with DIT for MS participants who developed spasticity: the genu or the posterior limb in the internal capsule, the rostral brainstem, and the callosal radiations cross interleaving with corticospinal tracts (16). Another small-sized study evaluated the impact of intermittent theta brain stimulation on MS participants with spasticity and showed the relevance of resting-state fMRI in highlighting the treatment effect on spasticity with a functional reorganization of the primary motor cortices, favoring connections of the contralateral primary motor cortex to other cerebral regions (17).…”
Section: Assessment Of the Spasticity-plus Syndrome With Imagingmentioning
confidence: 99%